PENERAPAN STRATEGI PEMBELAJARAN AKTIF SEPAK BOLA VERBAL UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROLISIS GARAM DI KELAS XI IPA SMA NEGERI 10 PEKANBARU - Wulandari, Annisaul Khasanah Wulandari Khasanah; Amran, Elva Yasmi Amran Yasmi; Copriady, Jimmi Copriady Jimmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The aim of this research is to improve student achievement on the subject of salt hydrolysis in class XI natural sciences (IPA) Senior High School (SMAN) 10 Pekanbaru trough the applying active learning football verbal strategy. This research is experimental study with pretest-posttest design. The research was conducted from Maret 2015 - April 2015. The population consisted of five class and the sample consisted of two classes of grade class XI IPA 4 as an class experimental and the class XI IPA 5 as an class control randomly selected after homogeneity test. Class experimental applied active learning Football Verbal strategy while the class control conducted discussions. The analysis technique used t-tes with dk = 35 + 36 = 69 (α = 0,05). Based on end of the data processing obtained trithmetic> ttable (4.3286> 1.994) means the application of active learning football verbal strategy can improve student achievement on the subject of salt hydrolysis in class XI IPA SMAN 10 Pekanbaru. The increase learning achievement in class experimental of 20,62%Keywords: Active Learning Football Verbal strategy, Learning Achievement, salt